Dynamics Of Average Cost Of Capital (Wacc) In Mining Companies ASEAN Exchange: Commodity Perspective And Economic Changes Due To The Covid-19 Pandemic - Umar Rivaldy Pulukadang; Dewi Hanggraeni (UNIVED Press, 2026)
This study analyzes the dynamics of systematic risk (Beta), expected rate of return (Ke), and Weighted Average Cost of Capital (WACC) in 108 mining companies in ASEAN EXCHANGE, comparing the pre-COVID-19 period (2017–2019) andPost-COVID-19 (2020–2022). This study uses quantitative analysis to examine the effects of commodity classification and exchange location (ExchangeCode), including ANOVA and ANCOVA. The results show high Beta variability. Although the average sector Beta increases post-pandemic, the change between periods is not statistically significant at the firm level. ExchangeCode is consistently a substantial determinant of Beta, while Commodity and Status are generally insignificant. Aggregate expected returns (Ke) increase moderately post-COVID, with varying trends across commodities. Beta is shown to be the dominant predictor of Ke, followed by ExchangeCode, which has a significant effect, while other factors have little impact in the ANCOVA model. The average sector WACC decreases slightly post-COVID, likely due to lose monetary policy, but significant variation across exchanges remains (e.g., high IDX, low SGX). The effects of exchange Code, Commodity, and Status on WACC are statistically proven to be small. In conclusion, exchange location and systematic risk (Beta) are crucial factors that influence the cost of equity capital and risk profile of ASEAN mining companies, which are more dominant than commodity type or uniform impact of the pandemic. Changes in WACC are more macroeconomic, but the effect is heterogeneous across markets.